Current Ripple Amplitude Measurement in Multiphase Power Converters - Cervellini, María Paula (2017)
Improvements in the total current ripple in interleaved power converters are mainly determined by differences between the phase inductor values. Several methods have been presented in the literature to mitigate this problem, which requires the knowledge of the relative current ripple amplitude. However, in these methods, the measurement of such an amplitude is not addressed. This characteristic is difficult to measure because of the switching noise and the necessity to precisely locate the current waveforms peaks, despite the switches and drivers delay. Furthermore, the above-mentioned methods either perform the correction in real time or in a self-commissioning state. Therefore, it is necessary to implement the amplitude measurement in the same platform as the current control, which implies that the computational overhead should be minimized. This work presents a methodology for the measurement of the ratio among phase current ripple amplitudes in the frequency domain. The proposal allows us to precisely determine this characteristic, with a reduced sampling frequency and high noise immunity. Experimental tests on a four-phase buck converter validate the proposal.